2013
DOI: 10.1016/j.cell.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Rif1 and Rif2 Shape Telomere Function and Architecture through Multivalent Rap1 Interactions

Abstract: Yeast telomeres comprise irregular TG₁₋₃ DNA repeats bound by the general transcription factor Rap1. Rif1 and Rif2, along with Rap1, form the telosome, a protective cap that inhibits telomerase, counteracts SIR-mediated transcriptional silencing, and prevents inadvertent recognition of telomeres as DNA double-strand breaks. We provide a molecular, biochemical, and functional dissection of the protein backbone at the core of the yeast telosome. The X-ray structures of Rif1 and Rif2 bound to the Rap1 C-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
127
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(135 citation statements)
references
References 50 publications
8
127
0
Order By: Relevance
“…These results indicate that muRif1 simultaneously bound to both immobilized G4 and radiolabeled G4 DNA, supporting the idea that muRif1 could hold together multiple G4 DNA molecules. In budding yeast, association of Rif1 with chromosomal DNA is thought to be mediated by its binding to Rap1 protein (27). In contrast, the C-terminal domains of human and mouse Rif1…”
Section: Simultaneous Interaction Of Murif1mentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that muRif1 simultaneously bound to both immobilized G4 and radiolabeled G4 DNA, supporting the idea that muRif1 could hold together multiple G4 DNA molecules. In budding yeast, association of Rif1 with chromosomal DNA is thought to be mediated by its binding to Rap1 protein (27). In contrast, the C-terminal domains of human and mouse Rif1…”
Section: Simultaneous Interaction Of Murif1mentioning
confidence: 99%
“…A recent structural study revealed a tetrameric structure of the ScRif1 C-terminal domain (27), Cdc7-mediated phosphorylation events (11,13,28).…”
mentioning
confidence: 99%
“…In contrast to the yeast orthologue, mammalian Rif1 is not involved in telomere maintenance but has diverse roles in DNA repair and replication. Mammalian Rif1 was reported to accumulate at DNA doublestranded breaks (DSBs) 4 (5,6) and stalled replication forks (7). Recently, it was further shown that mammalian Rif1 is important for DSB repair pathway choice.…”
mentioning
confidence: 99%
“…Rif1 was initially identified as a telomeric protein in budding yeast, where it regulates telomerase access to the shortest telomeres (1)(2)(3)(4). In Saccharomyces cerevisiae, Rif1 telomeric binding depends upon its interaction with the sequence-specific DNA-binding protein Rap1.…”
mentioning
confidence: 99%
“…Rif1 (Rap1-interacting factor 1) was originally identified as a telomeric chromatin component required for telomere length regulation in budding yeast through its physical interaction with Rap1 (Hardy et al 1992;Shi et al 2013). It has since been demonstrated that S. cerevisiae Rif1 suppresses activation of the DNA damage checkpoint near telomeres (Xue et al 2011;Ribeyre and Shore 2012) and affects telomere replication time (Lian et al 2011).…”
mentioning
confidence: 99%